Analisis Kualitatif Persepsi Mahasiswa terhadap Penggunaan Machine Learning sebagai Pendukung Pembelajaran - Alex Septama Sihite; Judea Tirta Jordan Simamora; Octav Kornelius Hutagaol; Marcel Alezandro Sihombing (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
The development of Artificial Intelligence (AI), particularly Machine Learning (ML), has had a significant impact on the world of education as a supporter of the learning process. This study aims to analyze students' perceptions of the use of Machine Learning as a supporter of Artificial Intelligence-based learning. The study used a descriptive qualitative approach with data collection techniques through Likert scale questionnaires and interviews. The research respondents were 50 students who had used Machine Learning-based applications in learning activities. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results showed that the majority of students had a positive perception of the use of Machine Learning. 80% of respondents agreed with the use of Machine Learning in learning, 12% were neutral, and 8% disagreed. Students considered that Machine Learning facilitates understanding of material, accelerates task completion, increases learning motivation, and supports independent learning. However, some students were still concerned about the potential for dependence on technology and reduced critical thinking skills if used excessively. The results of the study indicate that Machine Learning has great potential as a supporter of learning in higher education if used wisely and balanced with critical thinking skills and digital literacy. Keywords: Artificial Intelligence, Machine Learning, Student Perception, Learning, Technology Acceptance Model.